Peculiarities of Nostalgic Experiences of Women in a Pre-Trial Detention Center - G.A. Vartanyan; E.L. Soldatova; M.V. Likhanov; K.V. Bartseva; E.Yu. Tsvetkova (Психология и право)
The purpose of the study is to study the peculiarities of women’s nostalgic experiences in a situation of isolation. 78 women in a pre-trial detention center were studied using the following methods: WHO nostalgia questionnaire, author’s nostalgia content questionnaire, Big Five BFI-2-S, dark triad, WHO5 well-being questionnaire, method for diagnosing subjective well-being of a person, test of life-meaning orientations, an anxiety questionnaire and a method for diagnosing crisis symptoms. The value of nostalgia and the tendency towards it, as well as the significance of memories from the past, have been revealed. Women demonstrate a high level of anxiety, low locus of control of Self, locus of control of Life, a general indicator of meaningfulness of life, high rates of extraversion and conscientiousness and low rates of agreeableness, neuroticism, openness to experience, with a relatively high level of subjective well-being. The data showed a relationship between the value of nostalgia and the level of subjective well-being, locus of control of the self and agreeableness, as well as the tendency to nostalgia with the level of subjective well-being, anxiety and neuroticism. According to regression analysis, the characteristics of nostalgic experiences are influenced by subjective well-being, goodwill, as well as the locus of control “life” and “life process”. Probably, nostalgia can act as an adaptation resource for the individual.